Further Studies of Porcine Malignant Hyperthermia - Hall, L. W. (1972)
A non-lethal procedure for identifying pigs apt to develop malignant hyperthermia is described. Susceptible animals were exposed to a variety of anaesthetic and other agents and it was shown that thiopentone sodium and CT 1341 (Glaxo) afforded a measure of protection against the development of the syndrome. Pretreatment with procaine did not prevent the onset of the condition and the administration of procaine when muscle rigidity was present failed to prevent a fatal outcome. The syndrome was induced in susceptible animals by halothane, chloroform, and a combination of halothane with suxamethonium. The effects of cyclopropane in susceptible pigs could not be predicted, and other tests showed that suxamethonium alone would not induce muscle contracture. Pretreatment with lignocaine failed to prevent induction of the syndrome by halothane. We believe that the porcine syndrome may result from more than one defect and that in one particular type the most effective treatment is immediate cooling coupled with the administration of sodium bicarbonate.